2005
DOI: 10.1128/iai.73.7.4315-4322.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniaeAugments the Oxidized Low-Density Lipoprotein-Induced Death of Mouse Macrophages by a Caspase-Independent Pathway

Abstract: Chlamydia pneumoniae is a common respiratory pathogen that is associated with an increased risk of cardiovascular disease. However, the mechanisms by which C. pneumoniae contributes to cardiovascular disease have not been determined yet. C. pneumoniae infection may accelerate the death of cells within atherosclerotic lesions and contribute to the formation of unstable lesions. To test this hypothesis, the impact of C. pneumoniae infection on the death of lipid-loaded mouse macrophages was investigated. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…We repeated the same experiments in primary human placental fibroblasts and showed that pretreatment with pancaspase inhibitor, Z-VAD-FMK, blocked the cHSP60-induced apoptosis. These data support the findings of Yaraei et al (53) in RAW 264.7 cells and suggest that caspase-dependent and -independent pathways may play roles in cHSP60-induced apoptosis in trophoblasts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We repeated the same experiments in primary human placental fibroblasts and showed that pretreatment with pancaspase inhibitor, Z-VAD-FMK, blocked the cHSP60-induced apoptosis. These data support the findings of Yaraei et al (53) in RAW 264.7 cells and suggest that caspase-dependent and -independent pathways may play roles in cHSP60-induced apoptosis in trophoblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Dumrese et al (52) have shown that C. pneumoniae infection of human aortic smooth muscle cells results in cell death with both apoptotic and necrotic characteristics. In addition, in RAW cells, infection with live C. pneumoniae or exposure to heat-killed or UV-inactivated C. pneumoniae led to aponecrosis, which was mediated via caspase-3-independent mechanisms (53). In a recent elegant review of Chlamydia pathogenesis, Byrne and Ojcius (54) state that "Chlamydia can elicit both the induction of host cell death, or apoptosis, under some circumstances and actively inhibit apoptosis under others.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of vascular smooth muscle cells with C. pneumoniae resulted in the activation of a signal transduction profile that is typical of atherosclerosis and most probably mediated by transcription factor early growth response (EGR)-1 [87]. In the presence of LDL, C. pneumoniae can induce the formation of cholesterol-filled foam cells (an early marker of atherosclerotic lesions and oxidation of LDL) [87][88][89]. Cell destruction could result in local effects (i.e., in the vasculature) and could also result in a more generalised inflammatory response that is thought to be a risk factor in coronary heart disease (CHD) [87].…”
Section: Animal Models Of Atherosclerotic Disease and Chlamydia Pneummentioning
confidence: 99%
“…Cell destruction could result in local effects (i.e., in the vasculature) and could also result in a more generalised inflammatory response that is thought to be a risk factor in coronary heart disease (CHD) [87]. These effects could be mediated by Toll-like receptors [88,90]. It has also been suggested that other infectious agents (such as cytomegalovirus [91] and Porphyromonas gingivalis [90]) could play a role perhaps by acting synergistically with C. pneumoniae to promote atherosclerosis [91], although C. pneumoniae has been the primary focus in most of the cell-based or animal studies.…”
Section: Animal Models Of Atherosclerotic Disease and Chlamydia Pneummentioning
confidence: 99%
“…It is tempting to speculate that C. pneumoniae favors an oxLDL-induced necrotic commitment of the cells by way of increasing cellular stress and using bacterial caspase-independent mechanisms, such as the Bax activating pathway [1,8,10]. It was recently shown that subsequent C. pneumoniae infection of oxLDL-loaded macrophages augmented caspase-independent cell death [34]. Our data clearly indicate that infection of cells stimulated ROS production and, consequently, could increase the level of intracellular oxidized lipids known to be involved in oxidative stress-mediated cell death [15,18].…”
Section: Discussionmentioning
confidence: 99%